DESIGN MANAGEMENT PROGRAM APPLICATION FOR INTERNET ACCESS IN STMIK JAKARTA PUSYANET - Wahyudi Riadi; Eko Hadiyanto, SSI, MMSI Eko Hadiyanto, SSI, MMSI (Jurnal Sistem Informasi, 2000)
A medium used for the general course requires management to continuity ofoperations, not much different from the means of Internet access that is intended forstudents STMIK Jakarta. By using application programs created with Visual Basiclanguage, management of user identities, the use and timing of each user requests alist of all of them are stored in the database using Microsoft Access.